SOME MECHANICAL PROPERTIES OF DOUGLAS-FIR WOOD FROM BULGARIA (Innovation in Woodworking Industry and Engineering design, 2026)
The Douglas-fir is a perspective species for Europe, introduced in Bulgaria long ago. During this time many studies have been made on the growth and productivity of forests of this tree species. Mechanical properties are an important part in the design of timber structures and the calculation of processing regimes. The values given for the properties depend on the altitude and the location of the wood under study in the stem.The subject of the research in this study is the Douglas fir wood and the determination of some mechanical properties of the wood, which has been done for the first time in our country. Standard methods and test bodies were used to establish the mechanical properties in this study.